Assessment of Acquisition Methods for a Juvenile Literature Collection at a Research University. Issue 2 (3rd April 2022) - Kogut, Ashlynn; D'Aveta, Laura; Tabacaru, Simona
Abstract: This study assesses the content and usage of juvenile materials acquired via three acquisition methods by a research-intensive university library. The primary method of acquiring juvenile materials is an awards-based approval plan. Subject librarian selections and purchase suggestions from faculty, staff, and students are also used to acquire juvenile materials. Using acquisition reports, catalog records, and circulation data from four fiscal years (2017-2020), we examined how these three acquisition methods compared to each other in terms of title characteristics and patron usage. We found all three acquisition methods are needed to develop a collection that meets the needs of our users.